2003
DOI: 10.1126/science.1089342
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Inverse Doppler Effect

Abstract: We report experimental observation of an inverse Doppler shift, in which the frequency of a wave is increased on reflection from a receding boundary. This counterintuitive effect has been produced by reflecting a wave from a moving discontinuity in an electrical transmission line. Doppler shifts produced by this system can be varied in a reproducible manner by electronic control of the transmission line and are typically five orders of magnitude greater than those produced by solid objects with kinematic veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
151
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(156 citation statements)
references
References 11 publications
2
151
0
3
Order By: Relevance
“…This frequency shift can also have unusual magnitudes. Recently, this theoretical prediction was confirmed by an experimental observation of a reversed Doppler shift from a shock-like wave propagating through a periodic electrical transmission line [1]. While the experiment by Seddon and Bearpark was performed in an electrical transmission line rather than a photonic crystal, the physical origin of the effect in these two systems is closely related.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…This frequency shift can also have unusual magnitudes. Recently, this theoretical prediction was confirmed by an experimental observation of a reversed Doppler shift from a shock-like wave propagating through a periodic electrical transmission line [1]. While the experiment by Seddon and Bearpark was performed in an electrical transmission line rather than a photonic crystal, the physical origin of the effect in these two systems is closely related.…”
Section: Introductionsupporting
confidence: 53%
“…One of these explanations is due to SB [1,23] and the other is our theory described in the previous sections and in previous work [15,24]. These two theories provide quantitatively identical predictions in conditions of the experiment of SB, but provide differing predictions in other experimental regimes.…”
Section: Experimental Observation Of a Reversed Doppler Effectmentioning
confidence: 54%
See 2 more Smart Citations
“…This phenomenon is presently called the reverse Doppler effect. Several platforms have been reported to observe this effect for acoustic [2], radio frequency [3,4], and optical [5] waves. Recently, we found that travelling-wave field-effect transistors (TWFETs), originally introduced by McIver in 1965 [6], can support shock waves by applying properly designed decreasing and increasing kink-like voltages to the drain and gate lines, respectively [7].…”
Section: Introductionmentioning
confidence: 99%